Issues of forming yields and improving the quality of green fodder based on winter barley - N. I. Devterova (Новые технологии)
The effect of fertilizers on the yield and quality of green fodder based on winter barley was studied to identify optimal cultivation methods. The research was carried out in 2018–2020 on low-humus heavy-clay drained leached chernozems of Adygea. Double disking at 12–16 cm was used on five backgrounds of fertilizer application: 1. Control sample (0.0 kg/ha a.s.). 2. Background N24Р104 (128 kg/ha a.s.). 3. Background + N30 (158 kg/ha a.s.). 4. Background + N45 (173 kg/ha a.s.). 5. Background + N60 (188 kg/ha a.s.). The formation of productivity took place under conditions of nutritional deficiency. Nitrogen yield was 128.3–303.7; phosphorus yield- 43.7–48.9; potassium yield – 100.9–335.1 kg/ha. It was established that The average yield was established to vary from 3.9 to 15.2 t/ha. The effectiveness of fertilizers was noted. Reliable increases in yield were obtained (1.2–10.5 t/ha, NSR05 1.4–2.4 t/ha). A significant degree of dependence of the crude protein content was revealed (r 0.5; R2 0.29; increase in 14.5–21.2%), a strong correlation of digestible protein (r 0.719; R2 0.517; 12.4–18.2%) and crude fiber (r 0.96; R2 0.92; 23.6–34.8%) from increasing fertilizer standards. It was established that application of fertilizer dose of 188 kg/ha a.is. (N24P104 + N60), using a resource-saving method of soil cultivation, made it possible to obtain the highest level of yield for the varieties of Romance – 15.2 t/ha, Dobrynya – 14.7 t/ha, Kondrat – 14.2 t/ha, Carioca – 7.4 t/ha. This cultivation method was the most optimal and expedient economically and energetically. The payback of 1 kilo of a.s. of fertilizers with grass mixture yield was the highest: 56.5; 45.2; 50.4; 20.2 kg, with increase: 15930; 12750; 22 140; 5700 rub. Reduced energy intensity of the varieties of Dobrynya 2.35 – 1.7; Kondrat 3.11 – 1.84; Romance 3.10 – 1.74 GJ/t, indicated the effectiveness of cultivation techniques.